Nanoparticle drug delivery systems in hepatocellular carcinoma: A focus on targeting strategies and therapeutic applications - Sayali Pravin Metkar; Gasper Fernandes; Prerana D. Navti; Ajinkya N. Nikam; Ritu Kudarha; Namdev Dhas; Raviraja N Seetharam; Krishnan Venkata Santhosh; Bola Sadashiva Satish Rao; Srinivas Mutalik (Elsevier, 2023)
Hepatocellular carcinoma (HCC) is recognized as a global health issue accounting for millions of deaths every year. Surgery, liver ablation, and embolization therapy are amongst the conventional methods for treatment of HCC. Chemotherapy plays a major role in HCC therapy, however, owing to its conventional pharmacotherapy limitations, it necessitates the development of novel therapeutic strategies. In contrast, nanomedicines for HCC have shown remarkable prospects for solving these complications in HCC owing to their high stability, controlled release, and high drug loading capacity. This review gives an insight into the nano-constructs used for HCC treatment and its active and passive targeting strategies. This review also inculcates the various approaches for targeting the liver cells, its targeting moieties and the conjugation chemistries involved in surface functionalization. A brief description of various therapeutic approaches in the treatment of HCC has also been discussed.